Characteristics of Vitamin B12 Deficiency in Adult Chinese Patients with Type 2 Diabetes and the Implication of Metformin - Joyce, Chan Chee Wun; Florence, Chan Hoi Yan; Howard, Wong Ho Nam; Yip, Yeung Chun (IntechOpen, 2011)
None